2004
DOI: 10.1055/s-2004-824868
|View full text |Cite
|
Sign up to set email alerts
|

Akzeptanz eines Patientenpasses in der Sekundärprävention der koronaren Herzkrankheit

Abstract: The acceptance of a passport is low, because fewer than half the patients used it in connection with the secondary prevention of coronary heart disease. Therefore the health pass in its present form did not show up as a useful device in patient care, particularly in single persons and those of a low sociodemographic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…However, the two studies produced similar findings regarding the demographic characteristics of passport users and non-users. Like Völler et al [14], we found that older participants and those with higher levels of education tended to use the passport more often. Gender-specific differences were not detected in either of the two studies.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…However, the two studies produced similar findings regarding the demographic characteristics of passport users and non-users. Like Völler et al [14], we found that older participants and those with higher levels of education tended to use the passport more often. Gender-specific differences were not detected in either of the two studies.…”
Section: Discussionsupporting
confidence: 78%
“…To our knowledge, only one other study exists in which researchers investigated the acceptance and use of a patient passport for secondary prevention of heart disease using a similar methodology. In that study, by Völler et al [14], the passport was mainly used to document changes in physiological protective factors and risk factors over time. By contrast, our study mainly focused on user assessments of the passport by cardiac rehabilitees.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations